AL-SHIDQ DALAM KOMUNIKASI PERSPEKTIF AL-QUR`AN - Zulbadri Zulbadri (Jurnal Ulunnuha, 2018)
Morals is a noble deeds of a servant, and a reflection of the confidence and the knowledge that he has, so akhlak that characterizes a person's behavior in personal life, social state and nation. Al-Qur'an as guidance in-spoken, polite and guidance for all activities for those who do right. In this discussion the author discusses the kinds of al-shidq on morals, right in speaking and understanding words correctly, according to what it said was the actual reality. His opponent was kidhb lieAlusiy, syihabuddin mhd ibn Abdullah al-Husainiy, 2000, Ruhu al-Ma’aniy fi tafsir al-Qur’an al-‘Azhim wa sab’u al-Matsaniy, Muassasah ar-Risalah, Al-Biqai, Burhanudddin Abi al-Hasan Ibrahim bin Umar, Nizam ad-Durar  fi Tanasub al-Ayah wa as-Suwar, juz.7 Al-Bukhary, Muhammad bin Ismail bin Ibrahim bin al-Mughirah,al-Jami as-Sahih al-Musnad min hadis Rasulullah saw wasunnatih wa ayatih SahihBukhari, juz. 1Al-Husaini, Mohammed Rashid bin Ali Ridha bin Mohammed Shams al-Din bin Muhammad Bahauddin maula Ali bin Khalifa Kulmuny, 1990, Tafsir al-Qur’an al-Hakim (Tafsir al-Manar), Kairo, Al-Haiah al-Mishriyah al-Ammah lil kitabAl-Maraghi, Ahmad bin Mustafa, 1970, Tafsir al-Maraghi, Mesir, Darul Fikri, Al-Qurthubi, Abu Abdullah bin Muhammad  bi Ahmad bin Abi Bakr  bin Farah al-Anshari  al-Khuzraji Syamsuddi, 1994, Al-Jami’ al-Ahkam al-Qur’an ,Tafsir Al-Qurthubi, Kairo; Dar al-Kutb al-Nishriyah, Al-Qusyairiy, Abd al-Karim bin Hawzan bin Abd al-Malik, 1999, Lithaif al-Isyarah, Tafsir al-Qusyairy, Mesir:Al-Haiah al-Misriyah al-Amah lilkitab, Al-Sa’di, Abdurrahman bin Nasir bin Abdullah, 2000, Taisir al-Karim ar-Rahman fi tafsir kalam al-Mannan,  Muassasah ar-RisalahShihab, M Quraish, 2005, Tafsir al-Misbah Pesan Kesan dan keserasian al-Quran, Tanggaerang: Lentera Hati, cet IIIAl-Wahidi, Abu al-Hasan bin Ahmad, 1994, Al-Washit fi Tafsir al-Quran, Dar al-Kutut al-Ilmiyah, Beirut.Qutb, Sayyid, 1971, Fi Zilal al-Qur’an, Beirut, Dar el-FikrAl-Zuhaili, Wahba bin al-Mustafa, 1991, Tafsir Al-Munir fi ‘Aqidah wa  as-Syari’ah wa al-Manhaj Beirut, Dar Elfikri.